Motivasi Siswi Mengikuti Kegiatan Ekstrakurikuler Bola Basket Di Sma Negeri 5 Kota Jambi - Nadia, Puput; Ilham, Ilham; Yudho Prabowo, bangkit (Journal Score, 2026)
This study aims to analyze the motivation of female students in participating in basketball extracurricular activities at SMA Negeri 5 Jambi City. The background of this research is based on the importance of motivation as a key factor influencing students' participation, interest, and achievement in sports activities within the school environment. This study employed a quantitative descriptive method with a survey approach. The population consisted of 12 female students who actively participated in the basketball extracurricular program, and the sampling technique used was total sampling. The research instrument was a Likert-scale questionnaire designed to measure two dimensions of motivation, namely intrinsic motivation and extrinsic motivation. Data were analyzed using mean scores and percentages to determine the students' motivation levels.The results showed that, overall, the motivation of female students to participate in basketball extracurricular activities was categorized as high. However, a more detailed analysis revealed that intrinsic motivation was categorized as low, while extrinsic motivation was categorized as moderate. The novelty of this study lies in its specific focus on female students and its comparison of the roles of intrinsic and extrinsic motivation in basketball extracurricular participation. The findings indicate that external factors, such as family support, the school environment, facilities, and coaching, play a more dominant role than internal drives. This study provides new insights for developing more effective motivational strategies to enhance female students' participation and achievement in school sports activities.